Knowledge and Practices of Nursing Students towards total Pain Management in Terminally ill Patients in two Selected Nursing Institutions in Mbarara Municipality. A Cross-Sectional Descriptive Study. - Andrew Natwijuka; John Baptist Asiimwe (Student's Journal of Health Research, 2022)
Background:  Pain is the physical, social, spiritual, and psychological discomfort in a human being. The vast majority of people globally claim to experience body pain 95% at some point in their lives. Methodology:  A cross-sectional study was conducted using a quantitative approach. A total of one hundred forty-six (146) nursing students participated in the study and they were selected by a simple random sampling method Results:  One hundred forty-six (146) nursing students were selected to participate in the study. The majority of subjects were aged between 18 to 29 years (89.8%) and there were more females (68.0%) and were pursuing certificate level of Ugandan education 62 (42.2%). The overall findings from the study show that majority of the nursing students had good to excellent knowledge (84.6%). The majority had used the observation method to determine patients‟ pain (93.9%). Conclusion:  The study highlighted good knowledge and practices towards the assessment of pain among nursing students. Recommendation:  The results of the study identified gaps in practices of nursing students in total pain management and thus we recommend that stakeholders for nursing training institutions should give more time to practical lessons under observation to be able to evaluate students and correct errors in practice to be able to train competent nurses.